Bestlink College of the Philippines Bachelor of Library and Information Science: Vol.3, No.1B (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The College of the Philippines is committed to providing quality LIS education, which includes tracking the progress of its past BLIS graduates. This research measures the impact of their LIS studies on their professional lives and what future BLIS students can learn from them. Researchers conducted a tracer study to ensure that LIS professionals can continue their work during the current pandemic. They sent an online survey questionnaire to BLIS graduates from the Bestlink College of the Philippines to gather data relevant to the study. Due to the pandemic, all interviews were conducted through Messenger. The study found that most respondents were females between 20 and 24. Respondents aged 25-29, 30-34, 35-39, and over 40 were the least represented. Most respondents were single and employed. Most respondents found work within six months after graduation, mostly in the private sector. The majority of respondents said their current employment is not LIS-related. Responders said that some LIS professionals needed more training and understanding and that good budgeting is required to meet the needs of customers and librarians for library collection and resources. The researchers have suggested five steps to promote growth and development among BLIS students and graduates. These steps include providing career guidance to graduating BLIS students, employing effective advertising strategies for the Bestlink College of the Philippines' BLIS program, taking into account the needs of library personnel and administrators, assisting future graduates in achieving professional success, and seeking feedback and guidance from former BCP BLIS graduates. These measures aim to support BLIS students and graduates in overcoming the challenges posed by the COVID-19 pandemic.